Description of the complete larval development of Lysmata amboinensis (De Man) (Decapoda: Lysmatidae) reared under laboratory conditions - de Sousa, Lígia F.; Marques, Daniel; Leandro, Sérgio Miguel; Santos, Antonina Dos (Zootaxa, 2022)
Complete larval morphological descriptions are currently only known for three of the 48 species of genus Lysmata. The present study describes and illustrates the larval development of Lysmata amboinensis (De Man) reared under laboratory conditions. Lysmata amboinensis larval development is composed by a total of ten zoea and a decapodite stage.                The first zoeal stage larvae presents sessile eyes, a carapace with a pterigostomial spine and anterio-ventral marginal denticles, a long, slender, and pointed rostrum, an antennal exopod terminally articled, a pleon with five somites, the fifth one bearing a pair of dorso-lateral spines on the posterior margin, and a triangular shaped telson with 7+7 posterior processes. The decapodite resembles a smaller adult and has extremely long antennas (more than twice the total length of the decapodite), the first two pair of pereiopods with chela, first four pairs of pereiopods with reduced and entire exopods, and fully developed pleopods.                The morphological features of L. amboinensis are compared with those currently available for the larval stage of the genus Lysmata.